Literature Study: The Influence Of The Project Based Learning Model On Science Process Skills And Students' Creative Thinking Skills On Fluid Materials - Syifa Ramadhani; Joni Rokhmat; Denune Galang Prawira (Postgraduate Program, University of Mataram, 2026)
This study aims to analyze the influence of the project-based learning (PjBL) model on science process skills and students' creative thinking abilities in fluid materials through a literature study approach and bibliometric analysis. Data were collected using the Publish or Perish application with the keywords